STUDI LITERATUR: PENGARUH WORKING CAPITAL MANAGEMENT TERHADAP PERFORMA PERUSAHAAN - Lafasya, Khalifa -; Suntpiet, Kevin Matthew; Samuel, Samuel -; Meiden, Carmel - (Makro Jurnal Manajemen Dan Kewirausahaan, 2023)
This research was conducted to examine the correlation between Working Capital management and business performance and found that holistically, the empirical findings are consistent, suggesting that cash flow should increase investment in Working Capital, in order for Working Capital to increase and improve the performance shown by Earning Before Interest Tax and Management (EBITM). This research was conducted using a systematic literature study method, with the help of Publish or Perish (PoP) software applications and several websites such as Google Scholar. This Literature Study categorizes articles based on research year, research methodology and research theory. The research method used is Systematic Literature Review. Based on this literature study, we can conclude that research on the relationship between Working Capital and Company Performance will reach its peak in 2020, before declining again in 2021. The theory that is often used is agency theory; The type of study of Working Capital that is commonly used is quantitative; The results of this study reveal that Working Capital Management has an important influence on company performance.